Analysis of Factors Affecting The Success of Nutrition Improvement Programs for Primary School Children - Ngurah Mahendra Dinatha; Andi Subhan Amir; Nurul Hidayah; R.A Wigati; Anis Satus Syarifah (Postgraduate, University of Mataram, 2025)
The high rate of malnutrition in Indonesia, especially stunting in children, is caused by economic constraints, lack of nutrition education, and limited access to health services, which have an impact on children's growth, cognitive development, and academic achievement. The success of primary school nutrition improvement programs is influenced by factors such as community involvement, policy support, and parents' and teachers' understanding of nutrition, although they still face implementation challenges that need to be overcome for long-term effectiveness. This research method uses a quantitative approach with surveys and statistical analysis to examine the factors that affect the success of the nutrition improvement program in grade 1 elementary school students in three schools in Purworejo District. With 106 respondents, data were analyzed using Pearson correlation, and linear regression through SPSS 27. The results of the t-test showed that the factors that affect the success of the nutrition improvement program have a significant influence on the success of the program (t count = 5.164; Sig. = 0.000 < 0.05). In addition, the results of the F test (F count = 26.666; Sig. = 0.000) confirmed that the regression model used was statistically significant so that the independent variables together affected the success of the program. The success of school nutrition programs relies on collaboration between parents, teachers, schools, and the government to improve nutritional knowledge and food availability. Policy support, including healthy food subsidies and training, is essential for ensuring the program's long-term sustainability.